Design and Performance of The Raspberry Pi Control System on Packaging Machine Capacity 2400 Pcs/h - Kriswanto, Kriswanto; Karsan, Karsan; Al-Janan, Dony Hidayat; Roziqin, Ahmad; Hangga, Arimaz; Fathoni, Khoirudin; Wijayanto, Bagus (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2021)
Technology Development in the era of industry 4.0 is characterized by the use of automatic technology machines. But in small and middle-scale industries still use the conventional machine. Low-cost packaging machines need to be developed by utilizing the Raspberry Pi control system. The purpose of this research is to design, produce, and test the performance of powder packaging machines with the Raspberry Pi control system. This research uses an experimental research model with observational techniques in the form of a performance test. This research resulted in the design of the Raspberry Pi control system on a powder product packaging machine with a capacity of 240 pcs/hour. Based on the results of the control system performance test, it was found that the packaging was running well and consistent. From the rotation and stop pause of the stepper motor which has been set, it produces an average weight of the packaging and its contents weigh 13.737 grams. The difference in weight of the average product with the highest weight and the lowest weight is 0.063 grams and 0.057 grams. With a difference of less than 0.1 gram, it indicates that the weight resulting from packaging sugar products is good and consistent. In the pressing process, the temperature sensor takes temperature readings correctly, so that the heater can reach the press temperature of 1500C. Based on the trials and calculations that have been done, it is obtained 2,640 packages within 1 hour. This amount fulfills the initial target of designing a powder product packaging machine with Raspberry Pi control.